2019
DOI: 10.1186/s12909-019-1487-0
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of self-perceived cultural responsiveness in entry-level physiotherapy students in Australia and Aotearoa New Zealand

Abstract: Background Ensuring physiotherapy students are well prepared to work safely and effectively in culturally diverse societies upon graduation is vital. Therefore, determining whether physiotherapy programs are effectively developing the cultural responsiveness of students is essential. This study aimed to evaluate the level of self-perceived cultural responsiveness of entry level physiotherapy students during their training, and explore the factors that might be associated with these levels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
2
6
0
1
Order By: Relevance
“…Of note the students self-rated their baseline cultural competency at a relatively high level before the program, presumably due to social desirability bias. These high ratings are consistent with other studies in junior healthcare students [ 36 , 49 ]. The focus of the study was on the increase of their perceived skills after the program.…”
Section: Discussionsupporting
confidence: 93%
“…Of note the students self-rated their baseline cultural competency at a relatively high level before the program, presumably due to social desirability bias. These high ratings are consistent with other studies in junior healthcare students [ 36 , 49 ]. The focus of the study was on the increase of their perceived skills after the program.…”
Section: Discussionsupporting
confidence: 93%
“…The study suggests that clinical practicum with diverse populations did not increase cultural competency but that cultural competence was lower during and after practicums. Te and colleagues (2019) reported the same findings with physiotherapy students in Australia and New Zealand. However, one study done in Thailand reported the opposite: that clinical practicums with people from different cultural backgrounds improved students’ cultural competency (Khongsamai & Intarakamhang, 2020).…”
Section: Discussionsupporting
confidence: 63%
“…Therefore, none of the studies among health care students explored objective health care outcomes. A study by Te et al (2019) has shown an inverse relationship between weeks of clinical placement and perceived cultural competency, but the study’s focus was not on cultural competency directly related to First Nations peoples. A similar comparison among health care professionals’ years of experience and perceived cultural competency could not be made as the reviewed articles did not analyse participant characteristics with respect to these outcomes.…”
Section: Discussionmentioning
confidence: 99%